Intraparotid Superficial Temporal Artery Arteriovenous Malformation Causing Persistent Pulsatile Tinnitus. Issue 7 (August 2020) - Selleck, Anne Morgan; O'Connell, Brendan; Patel, Samip; Clark, Joseph Madison
Abstract : Objectives: This article discusses the diagnosis, imaging workup, and management of a rare cause of pulsatile tinnitus: intraparotid arteriovenous malformation. Patient: A single patient with a superficial temporal arteriovenous malformation diagnosed by carotid duplex causing pulsatile tinnitus that failed initial surgical management. Repeat imaging failed to identify a cause for the persistent tinnitus. Intervention: Reoperation with a parotid approach based on physical exam findings. Results: Removal of a more proximal arteriovenous malformation in the parotid gland resulted in long-term resolution of the patient's pulsatile tinnitus. Conclusions: Physical examination is essential in the workup and management of pulsatile tinnitus. Imaging is a useful adjunct in the diagnosis of pulsatile tinnitus but should not be solely relied upon.